Mikroplastik pada Sedimen di Pantai Kartini Kabupaten Jepara Jawa Tengah - Azizah, Pramita; Ridlo, Ali; Suryono, Chrisna Adhi (977-2407769)
Microplastic is plastic waste that is less than 5 mm in size and can accumulate in sediments. This study aims to determine the contaminant of microplastics in coastal Kartini sediments, Jepara. Sediment samples were taken in November 2019 with a purposive sampling method using sediment cores at 3 different stations namely the TPI River Estuary (Fish Auction Place), the LPWP River Estuary (Coastal Development Institution), and the BBPBAP River Estuary (Central Brackish Aquaculture Fisheries Center ), at 3 points inside it is 20 cm, 40 cm and 60 cm. The sample is dried and then separated based on grain size using a sieve shaker. Sediments trapped in 0.3 mm sieve size, taken as much as 50 g then immersed in 200 mL 30% H2O2 for 24 hours and then dried. Microplastic is separated from the sediment with 200 ml NaCl Ï = 1.2 g / cm-3, and the remainder the residue is immersed in 200 ml of ZnCl Ï = 1.5 g / cm-3. The number, shape, color and size of the microplastic were observed using the SZ 61 olympus microscope with a magnification of 10 x 10. The results showed that the most microplastics were found in the estuary of the TPI River (Fish Auction Place), namely 643 particles, followed at the estuary of the BBPBAP River (Center for Aquaculture Fisheries) Brackish) 499 particles and at least at station 2 there are 438 particles. The microplastic form is dominated by 506 fragments of particles, while the least microplastic is a pellet that is 295 particles. The microplastic color is dominated by brown as many as 466 particles, while the microplastic color is the least pink and clear as much as 2 particles / 50 g of dry sediment. The largest microplastic size is 208.29 Âµm and the smallest size is 6.21 Âµm.Â ABSTRAK: Mikroplastik adalah sampah plastik yang berukuran kurang dari 5 mm dan dapat terakumulasi pada sedimen. Penelitian ini bertujuan untuk mengetahui kandungan mikroplastik di sedimen pantai Kartini, Jepara. Sampel sedimen diambil pada bulan November 2019 dengan metode purpossive sampling menggunakan sediment core pada 3 stasiun yang berbeda yaitu Muara Sungai TPI(Tempat Pelelangan Ikan), Muara Sungai LPWP(Lembaga Pengembangan Wilayah Pantai), dan Muara Sungai BBPBAP(Balai Besar Perikanan Budidaya Air Payau), pada 3 titik kedalamanyaitu 20 cm, 40 cm, dan 60 cm. Sampel di keringkan kemudian dipisahkan berdasarkan ukuran butir menggunakan sieve shaker. Sedimen yang terjebak dalam sieve ukuran 0,3 mm, diambil sebanyak 50 g kemudian direndam dalam 200 mL H2O2 30% selama 24 jam lalu dikeringkan.Mikroplastik dipisahkan dari sedimen dengan Â 200 ml NaCl Ï = 1,2 g/cm-3, dan sisa residu nya direndam dalam 200 ml ZnCl Ï =1,5 g/cm-3. Jumlah, bentuk, warna dan ukuran mikroplastik diamati menggunakan mikroskop olympus SZ 61 dengan perbesaran 10 x 10. Hasil penelitian menunjukkan mikroplastik terbanyak ditemukan di Muara Sungai TPI (Tempat Pelelangan Ikan) yaitu 643 partikel/50 g sedimen, diikuti pada Muara Sungai BBPBAP (Balai Besar Perikanan Budidaya Air Payau) 499 partikel/50 g sedimen dan paling sedikit pada stasiun 2 berjumlah 438 partikel/50 g sedimen. Bentuk mikroplastik di dominasi fragmen 506 partikel/50 g sedimen, sedangkan mikroplastik yang paling sedikit adalah pelet yaitu 295 partikel/50 g sedimen. Warna mikroplastik di dominasi warna coklat sebanyak 466 partikel/50 g sedimen, sedangkan warna mikroplastik yang paling sedikit merah muda dan bening sebanyak 2 partikel/50 g sedimen kering. Ukuran mikroplastik terbesar adalah 208,29 Âµm dan ukuran terkecil adalah 6,21 Âµm.